Financial Report Format Development Base on Financial Accounting Standard of Indonesia for Snake Fruit (Salaccazalacca (Gaert.) Voss.) Supply Chain - Mutiara Nanda Harizca; Adi Djoko Guritno; Agung Putra Pamungkas (APTA and DTIP FTP UGM, 2020)
Business practice of Snake Fruit in Sleman Region especially in Turi, Tempel, and Pakem District is potential due to high productivity reaching 97.61% from total production in Sleman Region. One of the problems faced along supply chain is less financial document to support decision making. This research aims to develop financial report format base on Indonesia Financial Accounting Standard adjusted to the need of each tier in snake fruit supply chain. There are three main stages in this research, they are identifying snake fruit supply chain and its financial need, developing of financial report, and measuring the acceptance of developed form in each tier. The result shows developed financial report acceptance percentage of farmer is 81.98%, middleman is 80.67%, seller is 78.24% and association is 86.43%. The acceptance then describes into highly positive acceptability